FGFR2/STAT3 Signaling Pathway Involves in the Development of MMTV-Related Spontaneous Breast Cancer in TA2 Mice - Du, Jiaxing; Zhao, Qi; Liu, Kai; Li, Zugui; Fu, Fangmei; Zhang, Kexin; Zhang, Hao; Zheng, Minying; Zhao, Yongjie; Zhang, Shiwu (Frontiers in Oncology, 2020)
Our previous study confirmed that fibroblast growth factor receptor 2 (FGFR2) expression increased in spontaneous breast cancer (SBC) compared to that in matched normal mammary gland tissues of TA2 mice. The present study focused on the function of the FGFR2/STAT3 signaling pathway in the initiation of SBC. Serum and normal mammary gland tissues of TA2 mice with different times of pregnancy and SBC were collected and the expression of FGF3, FGFR2, STAT3, p-STAT3Ser705 and p-STAT3Ser727 were detected. The proliferation, invasiveness, and migration of tumor cells were compared before and after cryptotanshinone and Stattic treatment. Downstream protein expression of STAT3 was also studied in MA-891 and TA2 xenografts. Tissue samples from 139 cases of breast cancer were analyzed. We confirmed that MMTV-LTR amplification, and FGFR2, p-STAT3Ser705, p-STAT3Ser727 expression in the breast tissue of TA2 mice increased with the numbers of pregnancies and were the highest in SBC. Serum FGF3 expression was higher in SBC than the levels in TA2 mice with different numbers of pregnancies. After STAT3 was inhibited, MA-891 proliferation, invasiveness, and migration decreased and the expression levels of STAT3, p-STAT3Ser727, p-STAT3Tyr705, Bcl2, cyclin D1, and c-myc in MA-891 and animal xenografts were also down-regulated. In human breast cancer, STAT3 expression was significantly higher in triple negative breast cancer (TNBC) than that in non-triple negative breast cancer (non-TNBC). Our results showed that the FGFR2/STAT3 signaling pathway may be related to SBC initiation in TA2 mice. Inhibition of STAT3 can decrease proliferation, invasiveness, and migration in MA-891 cells and TA2 xenografts.